Răspunsuri

2014-09-21T20:18:45+03:00
A - b = 327
a : 4 = b
a = 4b, inlocuim pe a in prima ecuatie
4b - b = 327
3b = 327 
b = 327 : 3
b = 109
a = 327 + 109
a = 436
verificare: 436 - 109 = 327
14 3 14
2014-09-21T20:24:58+03:00
A - b = 327
a : 4 = b
a = 4b, inlocuim pe a in prima ecuatie
4b - b = 327
3b = 327 
b = 327 : 3
b = 109
a = 327 + 109
a = 436
verificare: 436 - 109 = 327

a - b = 327
b este de 4 ori mai mic decat a
a = 4b
4b - b = 327
b = 327 : 3 => b = 109
a = 327 + 109
a = 327 + 109 => a = 436
10 4 10